The influence of cultural values on consumer buying behaviour: a case of the wine industry in South Africa - Chiswanda, Tafadzwa F (My University, 2020)
As of two decades ago, the South African wine industry has been experiencing an incremental decline in exports as a result of major social and environmental changes, as well as a global oversupply of wine. In light of these negative changes, the South African wine industry is now turning some of its focus towards the domestic market. The biggest challenge is that there is insufficient information on the South African wine consumer behaviour, especially the underlying cultural values. The purpose of this study was to review and understand the influence of cultural values (individualism/collectivism, masculine/feminine and extended/limited family) on wine consumers' buying behaviour based on the perceived influence of two extrinsic attributes (price and packaging) in South Africa. The study also briefly explored the impact of demographic variables (gender and age) on wine consumer behaviour. An online survey and pen-and-paper questionnaire were utilised to collect data from 151 wine consumers, primarily from Soweto and Sandton in Johannesburg. Data was analysed using multiple-linear regression conducted on IBM SPSS (Statistical Package for Social Sciences) version 25. The results of the study indicated that cultural values do have an influence on consumers’ purchase decisions. Consumers with individual and extended family cultural values were found to associate wine quality with price and packaging perceptions when purchasing wine, while consumers with collective and limited family cultural values did not believe there was a relationship between wine quality and the two perceptions (price and packaging). However, the value of masculine/feminine was not supported. The demographic variables did not show an impact on purchasing intent.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Culture; Masculinity/feminine and extended/limited family) consumer behaviour; Cultural values (individualism/collectivism); Price; Packaging; Emerging markets; SDG-8: Decent work and economic growth